The impact of warming Tibetan Plateau on the 2020 summer unprecedented Northeastern Pacific Marine heatwave - Xuefeng Han; Ping Zhao; Jiaxin Ye; Jiao Li (npj Climate and Atmospheric Science)
Abstract An unprecedented marine heatwave (MHW) struck the extratropical Northeastern Pacific during the summer of 2020. This study reveals that this event is characterized by a persistent atmospheric high-pressure anomaly in the MHW region, which leads to a decreased cloud cover, an increased surface shortwave radiation (SWR), a decreased mixed-layer depth, and an increased sea surface temperature (SST). The local net surface heat flux anomaly associated with the increased SWR primarily drives the increased SST, while the oceanic processes likely play a minor role. Both observations and simulations further demonstrate that the SST and high-pressure anomaly are closely associated with a large-scale wave train over the extratropical sector from Asia to the North Pacific which can be forced by the Tibetan Plateau heating change. According to our findings, the projection of a persistent warming Tibetan Plateau heightens the risk of escalating MHW events in the Northeastern Pacific under future scenarios.